Distinct ecological processes shape micro-eukaryotic generalists and specialists in a canal-disturbed wetland, Lake Weishan, China - Xinghao Li; Yunfeng Wang; Micah Dunthorn; Chengzhi Mao; Qiaoyi Kong; Saleh A. Al-Farraj; Weibo Song; Jie Huang (Water Biology and Security)
Micro-eukaryotic communities are highly sensitive to environmental changes, and their structure offers crucial insights into the impact of human activities on aquatic habitats. Despite their significance, the assembly mechanisms of micro-eukaryotic communities in lake ecosystems heavily influenced by human activities are not well understood. In this study, we utilized 18S rDNA amplicon sequencing to examine the biodiversity of micro-eukaryotes over a one-year period in Lake Weishan, one of the largest freshwater lakes in northern China. We analyzed the ecological processes governing community assembly among key ecological groups, specifically habitat generalists and specialists. Our findings revealed substantial temporal variation in microbial diversity and community composition, likely driven by water temperature, dissolved oxygen, and the concentrations of several ions (e.g., Ca2+ and F−). Notably, community assembly in this canal-disturbed lake was predominantly influenced by stochastic processes (58.18%) rather than deterministic processes (20.46%). Habitat specialists (425 operational taxonomic units, OTUs) exhibited significantly greater diversity compared to habitat generalists (189 OTUs) and were predominantly shaped by stochastic processes (52.47%). In contrast, habitat generalists were less influenced by these processes (17.69%). Altogether, these results suggest that the ecological processes governing micro-eukaryotic community assembly differ markedly between habitat generalists and specialists, primarily due to their varied adaptability to environmental changes.